Respuesta :

Given the expression

[tex]\frac{a^4b^{-5}}{c^{-3}d^6}[/tex]

To simplify the expression above, we convert all negative indices to positive indices

Applying the rule of indices

[tex]a^{-x}=\frac{1}{a^x}[/tex]

Applying the rule to the given expression gives

[tex]\begin{gathered} \text{Where b}^{-5}=\frac{1}{b^5}\text{ and} \\ c^{-3}=\frac{1}{c^3} \end{gathered}[/tex]

Substitute the above deduction into the given expression

[tex]\begin{gathered} \frac{a^4b^{-5}}{c^{-3}d^6}=a^4\times\frac{1}{b^5}\times\frac{1}{\frac{1}{c^3}}\times\frac{1}{d^6} \\ \text{Where }\frac{1}{\frac{1}{c^3}}=c^3 \\ =a^4\times\frac{1}{b^5}\times\frac{1}{\frac{1}{c^3}}\times\frac{1}{d^6}=a^4\times\frac{1}{b^5}\times c^3\times\frac{1}{d^6} \\ =\frac{a^4c^3}{b^5d^6} \\ \frac{a^4b^{-5}}{c^{-3}d^6}=\frac{a^4c^3}{b^5d^6} \end{gathered}[/tex]

Hence, the simplified form is

[tex]\frac{a^4c^3}{b^5d^6}[/tex]

ACCESS MORE